Hormonal Contraceptive Use and Affective Disorders: An Updated Review - Mengelkoch S; Afshar K; Slavich GM (Open Access Journal of Contraception)
Summer Mengelkoch, Kimya Afshar, George M Slavich Department of Psychiatry and Biobehavioral Sciences, University of California, Los Angeles, CA, USACorrespondence: Summer Mengelkoch, Email smengelkoch@mednet.ucla.eduAbstract: Hormonal contraceptives have given women historic freedoms and control over their fertility. At the same time, the potential side effects and unintended consequences of hormonal contraceptive use remain unclear due to a severe lack of funding and research. In this review, we summarize what is currently known about the impact of hormonal contraceptive use on mood symptoms, depression, and premenstrual disorders, and propose using the Social Signal Transduction Theory of Depression as a framework to generate predictions about the mechanistic pathways through which contraceptive use is associated with depression risk. The highest-quality evidence suggests that some types of contraceptives increase depression risk for some women. However, some contraceptives also appear to decrease depression risk in some instances. Key risk factors that predict depression following hormonal contraceptive use include age/age at onset of contraceptive use and mental health history/susceptibility. Hormonal contraceptives differ in ways that influence mood-related outcomes and can be used to treat depression in some women, especially those whose depression symptoms fluctuate across the cycle, indicating the potential presence of a premenstrual disorder. Looking forward, research, and funding for this research, is needed to elucidate the mechanistic pathways through which the use of different contraceptives impacts mood in different women to allow for a precision medicine approach to contraceptive treatment. In the meantime, health care providers should adopt patient-centered, “mindful prescribing” approaches to contraceptive counseling.Keywords: women’s health, hormonal contraception, depression, affective disorders, premenstrual disorders, mechanisms